GRAMMAR INSTRUCTION IN COMMUNICATIVE LANGUAGE TEACHING - Axmedjanova, Farida (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores the role of grammar instruction within the framework of Communicative Language Teaching (CLT). As language educators strive to strike a balance between form-focused instruction and meaningful communication, this study aims to provide insights into effective approaches for integrating grammar into CLT. The article discusses the impact of grammar instruction on language proficiency, learner motivation, and communicative competence.